The faces of freedom in the concepts of a liberal and non-liberal state - Przedańska, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The last decade has exposed the recession of freedom throughout the world. It arises from the latest Freedom in the World 2020 report that civil liberties and political rights have deteriorated in 64 countries, while only 37 have seen a slight improvement in these areas. The principles of liberal democracy (the rule of law, free elections, minority rights and freedom of expression) in Europe, historically the best-performing region in terms of freedom in the world, have come under serious pressure in recent years.In the article, starting from an analysis of the categories of freedom presented in many aspects, followed by a discussion of the assumptions and concepts of liberalism, as well as the political project referred to as non-liberal democracy, which has grown out of their criticism, the author identiﬁes the problem of instrumentalization and relativization of freedom, which leads to the restriction of freedom of speech, freedom of minorities, religious freedom and sexual freedom, replacing the individual freedoms of the citizens with the so-called collective freedom.
Keywords: wolność; demokracja; liberalizm; demokracja nieliberalna; autorytaryzm